Peran Guru Kristen Sebagai Penuntun: Sebuah Kajian Teologis Efesus 4:11-16 Dalam Konteks Pendidikan Kristen [The Role of Christian Teachers as Guides: A Theological Study of Ephesians 4:11-16 in the Context of Christian Education] - Sri Susianti Zega; Musa Sinar Tarigan (Diligentia: Journal of Theology and Christian Education, 2024)
The role of teacher as a guide is very significant in teaching, especially to equip students to know God through Christian education. Teachers guide the students to understand knowledge, attitudes, skills, and spirituality based on Biblical principles. But in reality, teachers do not teach the Bible principles in learning, teachers do not guide the students, and have lack of knowledge of the Bible. Teachers should have understood the significance of guiding students based on the Bible. Hence, the purpose of writing this article is to present the significant role of teachers as a guide through the theological study based on Ephesians 4:11-16 for the context of Christian education with literature study as the research method. Teachers must guide students based on the truth of God's Word, through imitating Jesus as the Great Shepherd. Christian teachers’ role as guide do not only stop at knowledge in academic learning, but to be an impact for students to be a part of service to God and to build others up as members of the body of Christ. Christian teachers must guide students to achieve, namely: the unity of the faith in Christ as God and Savior in true knowledge, thorough maturity, and growth in accordance with the fullness of Christ and to ensure to be not tossed around by the waves of false teaching that ignore The Lord. This article concludes that the teacher's role as guide is one form for equipping students to grow more mature in Christ. The author suggests that Christian teachers understand that teachers are God's calling to reveal God's truth to students so that their lives base on Bible teaching, and Christian teachers must understand the students' needs to know God and grow spiritually to become more like Christ.